THE EFFECT OF PRODUCT MIX AND COMPANY IMAGE ON PURCHASE DECISIONS ON E-COMMERCE SHOPEE - Yudhi Koesworodjati; Muhammad Insan Fadillah (Jurnal Riset Bisnis dan Manajemen, 2022)
This study aims to determine the effect of product mix and company image on purchasing decisions at Shopee e-commerce. The research method used is descriptive and verification methods with a total sample of 95 respondents. The results showed that there was a positive and significant influence between product mix and company image on purchasing decisions. The amount of influence of product mix and company image on purchasing decisions simultaneously is 70.6%, and the remaining 29.4% is influenced by other variables not examined. Partially, the effect of product mix on purchasing decisions is 54.3%, and the influence of company image on purchasing decisions is 16.3%, so it can be concluded that product mix has the greatest influence on purchasing decisions.